Isolation of fungi from the surface water of river - Sharma3, U. Kutti4, Shaista Parveen1*, S. Lanjewar2, K. (Journal of Experimental Sciences, 2011)
Water bodies play an important role in the stabilization of any civilization. India is facing a turbulent water future, as its major water source rainfall fluctuates widely, seasonally as well as regionally. Water body provides a large amount of easily accessible fresh water which is important for the stable commodity for any population. Raipur city is capital of Chhattisgarh state, situated in the fertile plains of Mahanadi River. For the study of fungal community present in river water, we have collected fungi from water, to understand the overall diversity among different taxonomic groups of fungi present, as well as their occurrence, frequency and contribution of the fungal species in the river. The quantitative and qualitative fungal composition of river water was surveyed monthly for a year i.e. March 2009 to February 2010. A variety of fungal strains was isolated and identified from the water of river. Out of a total 389 fungal colonies, 31 fungal species belongs to 20 fungal genera were isolated. Aspergillus niger was most frequent species with (83.33%), Rhizopus sp. (75%) followed by A. flavus and A. fumigatus with (58.33)% frequency. It was also found that maximum percentage contribution was observed for Aspergillus fumigatus (15.16%), which was followed by Aspergillus niger with a (09.51%) contribution.